Contact Lens Discomfort (CLD) Treatment with MY MASK Light Modulation® LED mask - Pavan Michielon, Enrico; Gheller, Pietro; Pinero, David; Stanco, Luca (Scandinavian Journal of Optometry and Visual Science, 2024)
The purpose of this study was to understand how the use of the light modulation LED mask MY MASK affects Contact Lens Discomfort (CLD). Forty-two (42) soft contact lens wearers with dry eye symptoms were recruited for a 3-week descriptive observational study. Treatment using the light modulation LED mask was applied three times, each lasting 15 minutes; on day 1, day 3 and after one week. Symptoms of CLD were quantified with the help of a specific questionnaire (CLDEQ-8) before and after treatment. Ocular surface and tear film measurements were conducted at baseline and 1 week after the last treatment. Visual acuity remained stable (0.00 LogMAR ± 0.10). The number of symptomatic contact lens wearers decreased by 43% (18 out of 42 subjects), as indicated by the CLDEQ-8 scores (t−test=5.14; p < 0.001) (R2=0.218). Non-invasive tear film breakup time (NIBUT) improved significantly. Before treatment, 70% of eyes (59 out of 84) showed a NIBUT of less than 10 s; after treatment, 26% had values below this cut-off (t-test=3.06; p=0.001) (R2=0.241). Meibography values did not change (t-test= 1.17; p= 0.121) (R2 = 0.872). TearScope showed considerable improvement in tear film lipid layer thickness and the data obtained through the Gland Evaluator also demonstrated an improvement. Treatment using light modulation LED mask could be an interesting option in improving the aspects that characterise CLD. Additional research is required to establish the reliability of the observed improvement and investigate the necessity of repeated treatments as a means of stabilising or sustaining satisfaction in contact lens wearers.